Uniform indium arsenide quantum dots formation - Lim, Kheng Boo, 1981-, author; Zulkafli Othaman, author; Rosnita Muhammad, 1972-, author; Shahrizar Roslan, author; Regional Conference Solid State Scince and Technology (23rd : 2007 : Johor Baharu)i (Skudai : Universiti Teknologi Malaysia, 2007)
PRZSL